A companhia estável de repertório de capa, espada e nariz: Cyrano de Bergerac (1985) nos palcos brasileiros - Duarte, André Luis Bertelli (2011)
This study proposes a narrow with some of the paths taken by the Brazilian theater in the 1980 s from the analysis of the play of Cyrano de Bergerac by Companhia Estável de Repertório in 1985, directed by Flávio Rangel and with Antonio Fagundes as the major character. Indeed, questions the relationship between History/Aesthetics, news settings of dialog Art/Society, Theater/Politics, proposing an increase of understanding about certain cultural practices in the period.